Proceedings of the 12th International Conference on Interaction Design and Children 2013
DOI: 10.1145/2485760.2485815
|View full text |Cite
|
Sign up to set email alerts
|

Engaging children in cars through a robot companion

Abstract: Having children as passengers in a car influences the parents' experience of driving. Concern for their safety often supersedes other considerations. When designing in-car solutions to address the special needs of children as passengers, one could aim for assisting the parents with this task. For such systems, it is important that the proposed solution is able to engage the children and keeps them from distracting the driver, while offering the children an interesting and meaningful way to spend their time in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Hiau et al [10] designed an in car entertainment system and found that having a physical robot companion to whom the children directed their attention proved better than a system without a physical companion. Furthermore, [2] showed that a robotic agent, used to help drivers with tasks such as managing phone and messages in a mock driving task, the robot agent helped reduce driver task load and promoted sociability better than a phone or a static agent.…”
Section: Related Workmentioning
confidence: 99%
“…Hiau et al [10] designed an in car entertainment system and found that having a physical robot companion to whom the children directed their attention proved better than a system without a physical companion. Furthermore, [2] showed that a robotic agent, used to help drivers with tasks such as managing phone and messages in a mock driving task, the robot agent helped reduce driver task load and promoted sociability better than a phone or a static agent.…”
Section: Related Workmentioning
confidence: 99%